2008
DOI: 10.1210/jc.2007-2042
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroperoxidase Antibody-Dependent Cytotoxicity in Autoimmune Thyroid Disease

Abstract: These results demonstrate that anti-TPO aAbs can damage cultured thyroid cells by ADCC and CDC mechanisms. The monocytes, via their FcgammaRI, are important effector cells in ADCC mediated by anti-TPO aAbs and may contribute with T cells to the destruction of thyroid gland in AITD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 25 publications
0
56
0
4
Order By: Relevance
“…We previously showed that TPO aAbs are, through both ADCC and CDC, able to damage human thyroid cells on binding to TPO expressed on the cell surface (Rebuffat et al, 2008). In this study, we hypothesised that human recombinant anti-TPO aAbs could be used to destroy thyroid tumour cells and thus to develop a complementary therapeutic approach in thyroid cancers.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…We previously showed that TPO aAbs are, through both ADCC and CDC, able to damage human thyroid cells on binding to TPO expressed on the cell surface (Rebuffat et al, 2008). In this study, we hypothesised that human recombinant anti-TPO aAbs could be used to destroy thyroid tumour cells and thus to develop a complementary therapeutic approach in thyroid cancers.…”
Section: Discussionmentioning
confidence: 95%
“…The expression of CD14, CD16 (FcgRIII), CD32 (FcgRII), CD64 (FcgRI) on the surface of the different effector cells (HL-60 and PBMC) was investigated using fluorescein-conjugated anti-human CD Ab (Miltenyi Biotech, Bergisch Gladbach, Germany and Pharmingen, Becton Dickinson, Franklin Lakes, NJ, USA) and analysed by flow cytometry analysis as previously described (Rebuffat et al, 2008). Monocytes and lymphocytes present in PBMC were identified by size/structure analysis.…”
Section: Cellsmentioning
confidence: 99%
See 3 more Smart Citations